Analisis Logam Merkuri (Hg) dalam Krim Pemutih Herbal Temulawak (Curcuma zanthorrhiza) dengan Metode Mercury Analyzer - Anita Agustina Styawan; Lenny Apriyaningsih; Dwi Joko Yulianto (STIKES MUHAMMADIYAH KLATEN, 2019)
Temulawak herbal whitening cream is one of the herbal whitening creams containing curcumin rhizome extract containing curcumin, demetoksikurkumin and bidemetoksikurkumin which can reduce hyperpigmentation (the skin becomes too dark). Mercury is a dangerous metal that in even small concentrations can be toxic. The use of mercury in whitening creams can cause a variety of things, ranging from changes in skin color which will eventually cause black spots on the skin, allergies, skin irritation and can be carcinogenic. The results of the study qualitatively indicated that sample A was positive containing mercury marked by an orange-red precipitate. Quantitatively, using Mercury Analyzer in sample A, the levels of mercury were 7,470.52 mg / kg or 7,470.52 ppm. The conclusions indicate that sample A is inappropriate or should not be used because it contains more than 1 mg / kg or 1 ppm of mercury.